Voluntary disclosure in Malaysian corporate annual reports - Mohd Ghazali, Nazli Anum (Malaysian Institute of Accountants, 2009)
The legal and regulatory framework for financial reporting in Malaysia is governed by the Companies Act 1965, accounting standards approved by the Malaysian Accounting Standards Board and the Bursa Malaysia Listing Requirements. Voluntary disclosure in the context of Malaysian listed companies can be defined as items of information which are not specified by any of the aforementioned pronouncements.